Directional property of radiation emitted from entangled atoms - Ooi, Chong Heng Raymond; Lee, H.W.; Kim, B.G.; Ikram, M. (Elsevier, 2009)
We investigate the directional property of photons emitted spontaneously from a partially-excited many-atom system. There exists a strong directional correlation between the emitted photons and the photons that have been absorbed by laser excitation and among all emitted photons themselves. Such a strong correlation arises from entanglement of W-type generated in the atomic system during the process of absorption and emission. (c) 2009 Elsevier B.V. All rights reserved.